A-119 Adverse Childhood Experiences, Cognitive Functioning, Depression, and Anxiety in Adulthood. (17th August 2022) - Bing-Canar, Hanaan; Khan, Humza; Stocks, Jane K; Lapitan-Moore, Franchezka; Phillips, Matthew S; Rauch, Andrew; Obolsky, Max; Cerny, Brian M; Soble, Jason R; Jennette, Kyle J; Resch, Zachary J
Abstract: Objective: Increasing evidence suggests that adverse childhood experiences (ACEs) predict neurocognitive dysfunction, possibly through direct (e.g., brain structure/function changes) and indirect (e.g., increased psychopathology risk) pathways. However, extant studies have focused on young and older adults, with limited understanding as to how ACEs affect cognitive health in mid-adulthood. Therefore, this study compared adults with high vs. low ACE scores on measures of cognitive performance and psychopathology. Method: This cross-sectional study included 211 adult patients (46.9% female; Mage = 44.9, SD = 17.1; Meducation = 13.8, SD = 3.0) consecutively referred for outpatient neuropsychological evaluation within a large, Midwestern academic medical center. A series one-way analysis of variances (ANOVAs) were conducted to compare high vs. low ACE groups on the Test of Premorbid Functioning (TOPF), Digit Span (DS), Trail Making Test-Part B (TMT-B), Rey Auditory Verbal Learning Test (RAVLT; Immediate and Long Delayed Recall), Beck Depression Inventory-II (BDI-II), and Beck Anxiety Inventory (BAI) scores. Results: Significant group differences were detected for BDI-II and BAI scores, F(1, 159) = 18.38, p.05. Non-significant cognitive measure findings cannot be attributed to group differences in premorbid functioning, as TOPF score also did not significantly differ by ACE group, p > 0.05. Conclusions: Results of this investigation suggest that greater ACEs increase risk of depression and anxiety, but not neurocognitive dysfunction, in adulthood.